2005
DOI: 10.2355/isijinternational.45.1915
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Creep Flow and Damage Properties of the Weakest Area of 9Cr1Mo-NbV Martensitic Steel Weldments

Abstract: In the present study, creep flow and damage behaviour of modified P91 steel weldments are investigated. Premature creep failure of weldments (with respect to base metal) occurs in the intercritical heat affected zone (ICHAZ). This microstructure is reproduced by thermal simulation applied to blanks cut from the base metal. Metallurgical investigations of what happens during the welding cycle show that the weakest part of the heat affected zone is heated slightly below complete austenitisation, with little (if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Figure 7 shows the dilatometric curves that account for the transformation to austenite during heating of the T91 and T9 steels when the heating rate is settled at 1, 30 and 50 ºC/s and the initial metallurgical state is the as-received one. As expected, the higher the heating rates, the more the temperatures A c1 and A c3 are shifted to higher values [26][27][28][29][30][31] . At the same time, for the 30 and 50 ºC/s cases, there is a clear change of slope in the intercritical portion of the curve at temperatures in the region of 900-925 ºC, suggesting that the transformation to austenite proceeds with two distinct regimes.…”
Section: 2supporting
confidence: 78%
“…Figure 7 shows the dilatometric curves that account for the transformation to austenite during heating of the T91 and T9 steels when the heating rate is settled at 1, 30 and 50 ºC/s and the initial metallurgical state is the as-received one. As expected, the higher the heating rates, the more the temperatures A c1 and A c3 are shifted to higher values [26][27][28][29][30][31] . At the same time, for the 30 and 50 ºC/s cases, there is a clear change of slope in the intercritical portion of the curve at temperatures in the region of 900-925 ºC, suggesting that the transformation to austenite proceeds with two distinct regimes.…”
Section: 2supporting
confidence: 78%
“…25,26,30 The specific heat treatment was conducted in a high temperature furnace, and the whole procedure can be divided into 3 steps. To circumvent the difficulty, a specific heat treatment process of the base material was conducted to obtain materials that are representatives of CGHAZ and FGHAZ.…”
Section: Description Of Welded Joint and Simulated Hazmentioning
confidence: 99%
“…The criterion has also been used by other researchers. 25,26,30 The specific heat treatment was conducted in a high temperature furnace, and the whole procedure can be divided into 3 steps. Firstly, the cylinder specimens with 12.5 mm diameter and 120 mm length were manufactured from a pipe.…”
Section: Description Of Welded Joint and Simulated Hazmentioning
confidence: 99%
“…Limited information is available on the effect of weld microstructure on inelastic deformation in P91 and related materials, due to the complexity of the IC‐HAZ microstructure and the difficulty of extracting test samples from IC‐HAZ. However, it is reported that the IC‐HAZ material has the lowest hardness compared with the other regions of the weld after PWHT . The IC‐HAZ is a partially transformed region, resulting in a mixture of metallurgical features .…”
Section: Introductionmentioning
confidence: 99%